DETERMINAN LITERASI DIGITAL MAHASISWA PADA ONLINE LEARNING DI MASA PANDEMIC COVID-19 - Dewi Surani; Umalihayati Umalihayati; Qonita Qonita (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
Nationally, the digital literacy index in Indonesia is still at the "medium" level. During the current pandemic, online learning is required. The purpose of this study is to find the determination of students' digital literacy in online learning?. This research is a descriptive quantitative study with a population of all students at Bina Bangsa University. Data were analyzed by descriptive statistical method. The results of this study indicate that the level of student literacy is not optimal. So that the development of online learning literacy